Empirical Analysis on Impact of Economic Value Added on Shareholder’s Value: A Perspective from Malaysian Construction Companies - Panigrahi, Shrikant; Yuserrie, Zainuddin; Noor Azlinna, Azizan (AENSI Publishing, 2015)
Background: Economic value added (EVA) is a concept developed Stern Stewart helps to identify true profitability of the organization due to consideration of cost of equity. Construction companies have been taken under consideration for this study. Objective: To provide an alternative measurement tool for the Malaysian construction companies that identifies true economic profit and enhance shareholder‟s value. Cross sectional secondary data are used of the selected companies for the period of 10 years from 2003 to 2012 Results: The result found significant influence of EVA on shareholder‟s value creation. It was also noticed from the trend analysis that from the 28 companies only 10 companies were having positive EVA whereas the remaining has destroying the shareholder value. The reason for negative EVA is high cost of equity. Conclusion: Thus in the proposed model it is confirmed that EVA as a value based performance tool dominates the shareholder value. Hence managers are suggested to pay more focus on the importance of EVA and its benefits for the shareholder‟s wealth creation and improve company performance.